2D Mg‐Cu Intermetallic Compounds with Nontrivial Band Topology and Dirac Nodal Lines. (23rd December 2021) - Wu, Rongting; Wu, Ze‐Bin; Božović, Ivan
Abstract: Synthesis of vertical heterostructures that include atomically thin layers of materials with topologically nontrivial energy bands is desirable for exploring exotic quantum states. Here, the authors report on atomic‐layer‐by‐layer deposition of magnesium on copper(111) surface by molecular beam epitaxy, monitored in situ by low‐energy electron microscopy and diffraction, and modeled by ab initio theory. It is found that a 2D MgCu2 intermetallic compound forms during initial Mg deposition and persists till a full monolayer of Mg is formed. Deposition of additional Mg triggers a phase transition from the commensurate MgCu2 to an incommensurate Mg2 Cu layer and enables growth of the second layer of Mg. Ab initio calculations indicate non‐trivial topology of the electron bands in the interfacial Mg2 Cu layer and the existence of Dirac nodal lines near the Fermi level. The new 2D Mg2 Cu material emerges as a promising platform to study new topological states of matter. Abstract : By atomic‐layer‐by‐layer deposition of magnesium on copper(111) surface, the authors construct a 2D MgCu2 intermetallic compound between magnesium and copper substrate, and further covert it to an incommensurate Mg2 Cu layer. Ab initio calculations reveal two Dirac nodal lines in the band structure of the Mg2 Cu layer and manifest it as a promising platform to study new topological states.